2017
DOI: 10.1158/1078-0432.ccr-16-1323
|View full text |Cite
|
Sign up to set email alerts
|

NNMT Silencing Activates Tumor Suppressor PP2A, Inactivates Oncogenic STKs, and Inhibits Tumor Forming Ability

Abstract: Purpose To identify potential molecular hubs that regulate oncogenic kinases and target them to improve treatment outcomes for glioblastoma (GBM) patients. Experimental Design Data mining of The Cancer Genome Atlas (TCGA) datasets identified Nicotinamide-N-methyl transferase (NNMT) as a prognostic marker for GBM, an enzyme linked to the reorganization of the methylome. We tested our hypothesis that NNMT plays a crucial role by modulating protein methylation leading to inactivation of tumor suppressors and ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 48 publications
5
63
0
Order By: Relevance
“…Among the up-regulated genes, we identified NNMT, LGALS3, PDLIM4, TUBA1C and ANXA2 as top five ( Figure 5D). NNMT silencing had been shown to activate tumor suppressor PP2A and inhibits tumor forming (Palanichamy et al, 2017). This was consistent with our result that it was up-regulated in GBM.…”
Section: Expression Perturbations Of Rna-binding Proteins During Gliosupporting
confidence: 93%
“…Among the up-regulated genes, we identified NNMT, LGALS3, PDLIM4, TUBA1C and ANXA2 as top five ( Figure 5D). NNMT silencing had been shown to activate tumor suppressor PP2A and inhibits tumor forming (Palanichamy et al, 2017). This was consistent with our result that it was up-regulated in GBM.…”
Section: Expression Perturbations Of Rna-binding Proteins During Gliosupporting
confidence: 93%
“…On the other hand, knockdown of NNMT in the ovarian carcinoma cell SKOV3 had the opposite effect as it increased SAM/SAH ratio, and global H3K9 and H3K27 trimethylation. Similar changes in methylation were also observed in one non-histone protein, protein phosphatase 2, suggesting that other cellular targets apart from histones might be differentially methylated by changes in NNMT expression and methyl donor levels [73,74]. These data provided a direct mechanistic link between NNMT and the regulation of epigenetic landscape of certain cancer cells.…”
Section: Nnmt and Methyl Donor Balancementioning
confidence: 63%
“…These authors concluded that NNMT over-expression was related to unfavorable clinic pathological features including tumor size, differentiation and TNM stage, and that it ultimately influences patient Xu et al [39] suggested that the activation of hepatocyte nuclear factor-1beta (HNF-1beta) contributed to NNMT up-regulation in papillary thyroid cancer cells and that the depsipeptide histone deacetylase inhibitor reduced NNMT and its catalytic activity [40]. Depsipeptide inhibition of NNMT is executed at the transcription level by down-regulating the HNF-1beta transcription activator [40] ( Figure 1), and it is suggested that the methylation mediated by NNMT can not only modify histone-dependent gene expression but it can also extend beyond histones to include tumor suppressor proteins such as PP2A [66]. NNMT could inhibit PP2A both at the epigenome and proteome levels and concomitantly activate pro-survival STKs.…”
Section: Role Of Nnmt In Cancermentioning
confidence: 99%